Mucosal innate response stimulation induced by lipopolysaccharide protects against Bordetella pertussis colonization - Errea, Agustina Juliana (2010)
Non-specific enhancement of the airways innate response has been shown to impair lung infections in several models of infection such diverse as influenza A, Streptococcus pneumoniae, and Aspergillus niger. Our aim was to evaluate whether a similar event could operate in the context of Bordetella pertussis respiratory infection, not only to enrich the knowledge of host-bacteria interaction but also to establish immunological basis for the development of new control strategies against the pathogen. Using a B. pertussis intranasal infection model and coadministration of different TLR agonists at the moment of the infection, we observed that the enhancement of innate response activation, in a TLR4-dependent way, could efficiently impair B. pertussis colonization (P < 0.001). While LPS from different microbial sources were equally effective in promoting this effect, flagellin and poly I:C coadministration, in spite of inducing expression of innate response markers TNFalpha, CXCL2, CXCL10 and IL6, was not effective to prevent B. pertussis colonization. Our results indicate that during the early stage of infection, specific anti-microbial mechanisms triggered by TLR4 stimulation are able to impair B. pertussis colonization. These findings could complement our current view of the role of TLR4-dependent processes that contribute to anti-pertussis immunity.